Do Real Estate Assets Maintain Their Real Values? Some Australian Evidence - Ta, Guy; J. Wilson, Patrick; Okunev, John (Asian Academy of Management (AAM), 1996)
Investors’ objectives in property and real estate investments would have their prime focus on the returns of their investments based on some optimal expectation that their investments maintain their values over time when the rate of inflation varies. Hence, the inflation hedging characteristics of real estate and property investments play an important role in the investors selection of their portfolios.